2013
DOI: 10.1007/s10461-012-0392-x
|View full text |Cite
|
Sign up to set email alerts
|

It Gets Better: Resolution of Internalized Homophobia Over Time and Associations with Positive Health Outcomes Among MSM

Abstract: Health disparities research among gay and bisexual men has focused primarily on risk and deficits. However, a focus on resiliencies within this population may greatly benefit health promotion. We describe a pattern of resilience (internalized homophobia (IHP) resolution) over the life-course and its associations with current health outcomes. 1,541 gay and bisexual men from the Multi-Center AIDS Cohort study, an ongoing prospective study of the natural and treated histories of HIV, completed a survey about life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 51 publications
10
86
1
3
Order By: Relevance
“…of psychosocial health problems 0 (n = 1,392) 1 (n = 812) 2 (n = 341) 3 or 4 (n = 129) [8] found that a greater proportion of gay men reported cessation of tobacco use than reported current daily tobacco use (26.9 vs. 25.7 %), indicating a widespread trend towards health promotion and recovery from an addiction that is very difficult to resolve. Gay and bisexual men have been shown to overcome internalized homophobia over the life-course despite existing in a context that promotes this form of selfloathing [9]. Most gay and bisexual men have also managed to avoid problematic drug use despite widespread use of recreational drugs generally perceived to be addictive [10,11].…”
Section: Evidence For Resilience Among Gay and Bisexual Menmentioning
confidence: 99%
“…of psychosocial health problems 0 (n = 1,392) 1 (n = 812) 2 (n = 341) 3 or 4 (n = 129) [8] found that a greater proportion of gay men reported cessation of tobacco use than reported current daily tobacco use (26.9 vs. 25.7 %), indicating a widespread trend towards health promotion and recovery from an addiction that is very difficult to resolve. Gay and bisexual men have been shown to overcome internalized homophobia over the life-course despite existing in a context that promotes this form of selfloathing [9]. Most gay and bisexual men have also managed to avoid problematic drug use despite widespread use of recreational drugs generally perceived to be addictive [10,11].…”
Section: Evidence For Resilience Among Gay and Bisexual Menmentioning
confidence: 99%
“…In South Africa, Graziano et al used a strength-based approach as a way of broadening the scope of HIV prevention by qualitatively applying a participatory-action research framework to identify both the adversities confronting MSM and the resilience-based protective factors they employ for coping with oppression [22]. In concurrence with the resiliency variables and constructs listed by Herrick et al Graziano identified socio-support, optimism, a supportive socionetwork, empathy, a gay-affirmative religion, self-acceptance of being gay, and spirituality associated with religiosity as strengths and protective factors adopted by MSM in South Africa for coping with different forms of adversity related to their being homosexual [17]. On the other hand, Ross and Anderson et al found religiosity to be associated with depression in Tanzanian MSM.…”
Section: Cultural Resilience Among Msm In Ssamentioning
confidence: 74%
“…Hence, in spite of the prevalence and impact of syndemic conditions on the health of MSM, synthesis of the evidence has shown that some MSM are resilient, especially in stopping tobacco use, overcoming internalized homonegativity (IH) and avoiding drug use [14,17,31,53]. This suggests that not all MSM who reside in a hostile environment and are exposed to multiple psychosocial health problems and their syndemic effects develop negative health outcomes.…”
Section: Resilience: a Corollary Of Syndemic Theorymentioning
confidence: 99%
“…The landmark Federal Supreme Court case, United States vs. Windsor (2013), which overturned the 1996 federal Defense of Marriage Act and allowed State Supreme Courts to decided marriage qualifications in their own states, the rescinding of the discriminatory military policy of "don't ask, don't tell," and possible passage of the Federal Employment Non-Discrimination Act are all promising signs of progress. [7,8] Gay marriage is on the legislative agenda in many states and is currently legal in 19 States and the District of Columbia, with state Supreme Courts considering anti-gay marriage laws unconstitutional on an almost monthly basis. However, discrimination and social stigma continue to exist for gay men, especially those who are young and/or from racial/ethnic minority populations.…”
Section: Estimating Mssipvmentioning
confidence: 99%